The impact of social assistance and capital expenditure on poverty levels in Aceh Province - Putri, Rizka Putri; Abral, Edi; Amri, Mustika (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to analyze the impact of social assistance and capital expenditure on poverty levels in Aceh Province from 2006 to 2023. The research employs a quantitative method using secondary data from the Statistics Indonesia (BPS) Aceh website and the Ministry of Finance’s DJPK website. Multiple linear regression analysis is used to examine the relationship between the independent variables (Social Assistance and Capital Expenditure) and the dependent variable (poverty levels). The results indicate that social assistance has no significant partial effect on poverty reduction, while capital expenditure has a significant impact. However, simultaneously, these variables do not exert a strong enough influence to reduce poverty jointly. Based on these findings, it is recommended that the government prioritize capital expenditure as an effective strategy to reduce poverty in Aceh, while also evaluating and enhancing social assistance programs for better impact.